2014
DOI: 10.1186/1742-2094-11-71
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal growth factor receptor inhibitor ameliorates excessive astrogliosis and improves the regeneration microenvironment and functional recovery in adult rats following spinal cord injury

Abstract: BackgroundAstrogliosis is a common phenomenon after spinal cord injury (SCI). Although this process exerts positive effects on axonal regeneration, excessive astrogliosis imparts negative effects on neuronal repair and recovery. Epidermal growth factor receptor (EGFR) pathway is critical to the regulation of reactive astrogliosis, and therefore is a potential target of therapeutics to better control the response. In this report, we aim to investigate whether blocking EGFR signaling using an EGFR tyrosine kinas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
47
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 56 publications
(71 reference statements)
4
47
0
Order By: Relevance
“…However, the conclusions from these studies are controversial. They applied EGFR inhibitors in injured spinal cord, and concluded entirely different results (Erschbamer, Pernold, & Olson, ; Q. Han et al, ; Li et al, ; Li et al, ; B. Liu & Neufeld, ; White et al, ). Inspiringly, EGFR activation exerts positive role in neurons (Ahmed, Read, Berry, & Logan, ; Wildering, Hermann, & Bulloch, ; Xu et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…However, the conclusions from these studies are controversial. They applied EGFR inhibitors in injured spinal cord, and concluded entirely different results (Erschbamer, Pernold, & Olson, ; Q. Han et al, ; Li et al, ; Li et al, ; B. Liu & Neufeld, ; White et al, ). Inspiringly, EGFR activation exerts positive role in neurons (Ahmed, Read, Berry, & Logan, ; Wildering, Hermann, & Bulloch, ; Xu et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Many investigators subsequently confirmed beneficial effects of treatments that break down or reduce CSPG production [32,79,93,113,116,125,152,161,195,360,361]. In 2006, Barritt et al reported that ChABC promotes sprouting in intact and injured spinal cords [16].…”
Section: Proteoglycansmentioning
confidence: 99%
“…Previous studies have showed that activation of EGFR in astrocytes at the injury site increases their reactivity, and therefore mediates glial scar formation (Liu and Neufeld ; Li et al . , ). We have previously demonstrated that in glioblastoma, GroA, an aptamer that inhibits cell surface nucleolin, prevented EGF‐induced receptor activation and its downstream signalling followed by reduced cell proliferation (Goldshmit et al .…”
Section: Discussionmentioning
confidence: 97%